A proposed approach to monitor private‐sector policies and practices related to food environments, obesity and non‐communicable disease prevention. (17th September 2013) - Sacks, G.; Swinburn, B.; Kraak, V.; Downs, S.; Walker, C.; Barquera, S.; Friel, S.; Hawkes, C.; Kelly, B.; Kumanyika, S.; L'Abbé, M.; Lee, A.; et al.
Summary: Private‐sector organizations play a critical role in shaping the food environments of individuals and populations. However, there is currently very limited independent monitoring of private‐sector actions related to food environments. This paper reviews previous efforts to monitor the private sector in this area, and outlines a proposed approach to monitor private‐sector policies and practices related to food environments, and their influence on obesity and non‐communicable disease (NCD) prevention. A step‐wise approach to data collection is recommended, in which the first ('minimal') step is the collation of publicly available food and nutrition‐related policies of selected private‐sector organizations. The second ('expanded') step assesses the nutritional composition of each organization's products, their promotions to children, their labelling practices, and the accessibility, availability and affordability of their products. The third ('optimal') step includes data on other commercial activities that may influence food environments, such as political lobbying and corporate philanthropy. The proposed approach will be further developed and piloted in countries of varying size and income levels. There is potential for this approach to enable national and international benchmarking of private‐sector policies and practices, and to inform efforts to hold the private sector to account for their role in obesity and NCD prevention.